Regional Training for East and Southern Africa - Grossi, Amanda; Dinku, Tufa; Faniriantsoa, Rija; Robertson, Andrew; Singh, Bohar (2021)
From November 1-6, 2021, the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) and the International Research Institute for Climate and Society (IRI) of Columbia University brought together representatives from 11 meteorological services across primarily East and Southern Africa and the IGAD Climate Prediction and Applications Centre (ICPAC) to conduct three parallel capacity building workshops in the context of Accelerating the Impact of CGIAR Climate Research for Africa project (AICCRA) project. The three workshops, which were hosted in Kampala, Uganda, were on the topics of 1) the Climate Data Tool (CDT) and Automatic Weather Station Data Tool (ADT); 2) the IRI Data Library and Maprooms; and 3) Seasonal Forecasting Approaches. Altogether, the workshops aimed to advance the availability, access, and use of high-quality climate information to anticipate, manage, and respond to climate-related disasters and longer-term climate change in the East and Southern Africa region.